Pendampingan proses produksi dan pemasaran pada peternak lebah madu rakyat: UMKM Madu Assyaffa di Desa Cipari Kabupaten Cilacap - Lingga Arti Saputra; Niken Hapsari Arimurti Susanto; Ari Budi Riyanto; Habib Ilham Majid; Pandhya Rizswaradana; Naziroh Putri Luftryani; Fadilah Riyan Anugerah; Rizki Widodo (Penamas: Journal of Community Service, 2026)
The community service program aims to address the challenges Assyaffa honey bee farmers face in production and marketing. The Assyaffa honey bee farm is located in Cipari Village, Cilacap Regency. The potential for plant vegetation and favorable natural conditions influence the availability of nectar and pollen, which, in turn, impacts honey harvest yields. However, the current production process still relies on manual and simple methods, resulting in very limited honey production. Honey sales are also very limited due to the continued use of conventional methods. The methods used in this program include outreach activities, assistance in production and marketing, and evaluation of activities carried out in stages within a predetermined timeframe. The results of the community service program show that implementing innovative hot-spray water centrifugal technology can increase Assyaffa honey production by 32%, from a previous total of 50 bottles to 66 in a single process. The process of mentoring marketing activities by implementing digital marketing media with more attractive, informative marketing labels can significantly increase sales of honey bee products.